THE EFFECT OF NOISE POLLUTION ON HEARING IN MARBLE FACTORY WORKERS OF AJMER, RAJASTHAN: A CASE STUDY - Kumari, Sumitra; Bafna, Garima; Singh, Yamini (International Journal of Clinical and Biomedical Research, 2015)
Introduction: The noise pollution is defined as the unwanted sound which is released into the environment. Noise induced hearing loss in an increasingly prevalent disorder that result from exposure to high intensity sound, especially over a long period of time. Materials & Methods: The present study has been conducted in the Department of Physiology and E.N.T. in a group of 60 subjects with 30 marble factory workers and 30 normal individuals. Results: Audiometric values were consistently lower in Normal than in marble factory workers. The differences were statistically significant among both sexes and that too for the parameters of Right and Left ear. Discussion and conclusion: In this study mild hearing loss was 20%, moderate hearing loss was 16.67%, moderately severe hearing loss was 36.67% and severe hearing loss 26.66%.This study also concludes that the presence of impact noise is more Hz to hearing irrespective of the duration of exposure but in workers exposed to continuous noise, the duration of exposure had a more prominent effect on the hearing loss. KEYWORDS: NIHL (Noise induced hearing loss); Pure tone audiometric testing.